Science for Africa’s future food security: linking agency and institutions in the food system - Dzudzor, Makafui I.; May, Julian D.; Mockshell, Jonathan (Springer, 2025)
Africa is not on track to achieve SDG 2, eradicating hunger by 2030. We argue that for meaningful and sustained food security, African people and institutions must be empowered to determine how their food systems are shaped. Drawing from a conceptual framework tailored to the African food system, we emphasise that regulative, normative, and cognitive institutions play a central role in structuring food systems on the continent. Agency is the means through which these institutions are activated and transformed. The profit-driven orientation and corporate concentration in the current food system impairs institutional capacity and local agency. To advance food security, food system transformation in Africa must be shaped by institutional pluralism, contextual specificity, and locally defined priorities.